A Comparative Study to Evaluate the Effect of Different Carbohydrates on the Stability of Immunoglobulin G during Lyophilization and Following Storage - Homa Faghihi 1, Sara Merrikhihaghi 1, Abdolhosein Ruholamini Najafabadi 1, Vahid Ramezani 2, Soroush Sardari 3, Alireza Vatanara 1 * (Tabriz University of Medical Sciences, 2016)
Background: Although the stabilizing effects of cyclodextrins (CDs) on the liquid protein formulations have been proven, there is no comprehensive data on evaluation of their effects on the lyophilized antibody powders. In this study, the influence of two CD derivatives namely beta-cyclodextrin (βCD) and hydroxypropyl beta-cyclodextrin (HPβCD) was compared with trehalose and mannitol regarding the molecular and thermodynamic stability of lyophilized IgG formulations as well as its biological activity. Methods: Sugars were separately added to IgG solutions and lyophilization process was conducted. In each group of carbohydrates, the formulations with lowest amounts of aggregates were examined regarding the biological activity. The storage stability of selected formulations was subsequently determined following 1 and 3 month of storage at 45 °C. Results: Trehalose and HPβCD in the ratios of 80% showed the most stabilizing effects by control of aggregated forms in the orders of 1.02% and 0.83%, respectively. Also, it was shown that trehalose and HPβCD could incomparably preserve IgG activity in values of 100% and 96.5%. The results of DSC and SEM analysis confirmed the existence of crystalline parts in mannitol and βCD formulations of antibody. During the storage time, the lowest rate constant of aggregation was observed in formulations containing trehalose 80% (0.16/month). All prepared formulations were beta-dominant and no fragmentation was detected. Conclusion: Molecular, thermodynamic and biological stability of lyophilized IgG was more desirable in the presence of trehalose and HPβCD in comparison to mannitol and βCD.